Psychological Approach On Sacrifice Conflict Of Anna’s Characters In The Novel “My Sister’s Keeper” - Humaeroah Humaeroah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
My Sister’s Keeper is a novel written by a New York Times Best Selling author, Jodi Picoult. The content of the novel tells the journey of a young girl making a sacrifice for her sister. This research aims to analyze the psychology of Anna doing a sacrifice for her sister. The type of this research is qualitative. The emerging conflict in main actors was analyzed using content analysis emphasizing on psychological approach. After reading and classifying My Sister’s Keeper Novel intensively, this study found the sacrifice conflict appeared in the novel. Based on the analysis, the novel shows internal and external conflict. Internal conflict (man vs self) of main character is a psychological conflict of Anna’s character about the sacrifice by doing donor of stem cell given to her sister and external conflict (man vs man) comes from her family.